Reflexion as a strategy in the process of life-long pedagogical education - Andrey V. Korzhuev; Vladimir S. Babaskin; A. R. Sadykova (Высшее образование в России)
Refleхive technologies in self-studying teacher’s activity focused on science «history inpersons» (personified science history), the analysis of pedagogics foundations, determination self-studying content and methods of its practical realization are discussed in the article.